Persistent IKKα phosphorylation induced apoptosis in UVB and Poly I:C co-treated HaCaT cells plausibly through pro-apoptotic p73 and abrogation of IκBα. (December 2018) - Otkur, Wuxiyar; Wang, Fang; Liu, Weiwei; Hayashi, Toshihiko; Tashiro, Shin-ichi; Onodera, Satoshi; Ikejima, Takashi
Highlights: UVB irradiation and TLR3 activation by Poly I:C induce apoptosis of HaCaT cells through the enhanced activation of IKKα. Abrogation of IκBα by the enhanced activation of IKKα partially contributes to apoptosis induced by UVB-Poly I:C. Tumor suppressor p73 contributes to UVB-Poly I:C induced apoptosis. Abstract: Toll-like receptor 3 (TLR3), a member of pattern recognition receptors, is reported to initiate skin inflammation by recognizing double-strand RNA (dsRNA) released from UVB-irradiated cells. Recently, we have discovered the NF-κB pathway activated by TLR3 is involved in apoptosis of UVB-Poly I:C-treated HaCaT cells. The real culprit for apoptosis has not been precisely identified since the system of NF-κB pathway is complex. In this study, we silenced main transcriptional factors in NF-κB family, RelA, RelB and c-Rel, but to our surprise the results show that none of them participate in apoptosis induction in UVB-Poly I:C-treated HaCaT cells. Therefore, we moved to investigate the apoptosis-associated molecules in the upstream of NF-κB pathway. We firstly checked the expression of IκBα, an NF-κB inhibitor. UVB (4.8 mJ/cm 2 ) and Poly I:C (0.3 μg/mL) co-treatment decreased IκBα expression level in a time-dependent manner. Silencing IκBα with siRNA further enhanced UVB-Poly I:C-induced cell death. We then investigated IκB kinase (IKK) complex that contributes to the degradation of IκBα. IKK is composed of IKKα, IKKβ and NEMO. Treatment with IKK-16, an IKKα/β inhibitor, significantly diminished UVB-Poly I:C-induced IκBα degradation and thus apoptosis. Silencing either IKKα or NEMO but not IKKβ with corresponding siRNA inhibited apoptosis. Tumor repressor p73, a homologue of p53, is reported to mediate IKKα-induced apoptosis in DNA damage response. Silencing p73 reduced cell apoptosis in UVB-Poly I:C-treated HaCaT cells. In summary, UVB and Poly I:C co-treatment activates IKKα and NEMO, which diminishes anti-apoptotic IκBα, resulting in enhancement of apoptosis through p73. The findings partially clarify the possible molecular mechanism of pro-apoptotic NF-κB pathway activated by TLR3 in the fate of UVB-irradiated epidermis.